„Wie ein Museumswärter“ - Andreas Vitáseks Kabarett(isten)retrospektiven - Huber, Mario (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
In contemporary Austrian cabaret, older shows are revived. What is special about this is that the original performers do not perform them; rather, younger cabaret artists perform the roles of previous generations. This article will use two works by cabaret artist Andreas Vitásek (1956–) to discuss the nuances of character portrayal associated with this approach. These provide clues as to how the art form is evolving. The discussions will focus on the relationship between stage and private persona, which is unique to cabaret and reflected in an interesting way in Vitásek’s shows. This highlights the close relationship between cabaret and other media, and how it is constantly evolving to distinguish itself from competing forms of entertainment. Examining Vitásek’s work reveals that contemporary cabaret incorporates a variety of theatrical and comedic performance styles. Artists deliberately employ these styles, which are recognized as such by audiences.